PENGARUH INDEPENDENSI, KOMPETENSI, RED FLAGS DAN TANGGUNG JAWAB AUDITOR TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN - Ni Putu Intan Eka Sari; Komang Fridagustina Adnantara (Universitas Triatma Mulya, 2020)
The development of an increasingly advanced economy and technology not only have a positive impact on the company but can also have a negative impact because it is used by those who want to benefit instantly.Cheating is often done, among others, manipulating the recording of financial statements, document removal, and profit mark-up that can be detrimental. For this reason, an independent third party that is considered capable of bridging the interests of agents and principals is needed. This research aimed to determine the effect of independence, competence, red flags and auditor responsibility on the auditor's ability to detect fraud. The grand theory used in this research is agency theory. The population of this study are auditors who worked on Public Accounting Firm (KAP) in Bali and listed on Directory of the Indonesian Institute of Certified Public Accountants, Indonesian Accountants Association East Indonesia Regional Coordinator in 2018. This study used a non-probability sampling technique that was purposive sampling with 59 respondents person. The colleted data using by questionnaire a four-point Likert scale to avoid multi interpretable, the central tendency effect is to reduce the bias of the research results on the neutral answers from the respondents. The data analysis technique used in multiple linear regression SPSS 20 (Statistical Pack age For the Social Sciences). The result of this research showed that independence, competence, red flags and auditor responsibilities have an influence on the auditor's ability to detect fraud.Keywords: independence, competence, red flags, auditor responsibility, auditor's ability to detect fraud.